Effectiveness of Variations of Diabetes Self-Management Education (DSME) on Self Care Behavior in Type-2 Diabetes Mellitus Patients in Tengku Chik Ditiro Hospital - Kartika Kartika; Ismuntania Ismuntania; Karmila Karmila; Fakhryan Rakhman (Masters Program in Public Health, Sebelas Maret University, 2022)
Background: Type 2 diabetes is one that is caused by an unhealthy lifestyle. such as too much sugar consumption and lack of activity. The purpose of this study was to analyze the effectiveness of variations in Diabetes Self-Management Education (DSME) on self-care behavior in Type 2 DM patients at Tengku Chik Ditiro Hospital.Subjects and Method: The type of research conducted in this study was a quasi-experimental pretest-posttest with controls. This research was conducted at Tengku Chik Ditiro Hospital, Aceh from February to August 2021. The study consisted of 3 groups, namely the control group, the group given DSME intervention, and the DSME variation group. The research was carried out in the sample in this study as many as 45 people with the provisions in each group 1:1:1 where each group there were 15 people. This study measures self care behavior before and after being given DSME. Data analysis was carried out using another paired-test and annova test.Results: After the intervention, the mean value of self-care behavior in the control group (Mean= 46.26; SD= 5.0), was higher than before (Mean= 43.33; SD= 8.24) but not statistically significant (p= 0.959), in the group. DSME (Mean= 66.67; SD= 5.77) was higher than before (Mean= 43.06; SD= 7.05), and statistically significant (p< 0.001), and in the variation group DSME (Mean= 68.46; SD= 6.92) was higher compared before (Mean= 44.7; SD= 8.72), and statistically significant (p< 0.001).Conclusion: DSME activities can help increase the ability of diabetic patients to carry out self-care behavior independently.Keywords: diabetes self management education, ankle brachial index, patientCorrespondence:Kartika. School of Health Science College Medika Nurul Islam. Jl. Cot Teungoh, Pidie, Aceh 24112, Indonesia. Email: dr.kartika85@gmail.com. Mobile: 082370882709.Journal of Health Promotion and Behavior (2022), 07(01): 77-85DOI: https://doi.org/10.26911/thejhpb.2021.07.01.08